Characterization of Electrically Conductive Adhesives to Enable Perovskite-Silicon Tandem Solar Cell Interconnection - Leonhard Böck; Torsten Rößler (SiliconPV Conference Proceedings)
The mechanical stability of interconnections in solar modules is crucial for their long-term performance. Electrically conductive adhesives (ECAs) offer a promising solution for the interconnection of perovskite-silicon tandem (PVST) solar cells due to their low-temperature processibility. In this study, the influence of low curing temperatures on the mechanical and electrical properties of ECAs was investigated to assess their suitability for PVST technology. Four commercially available ECAs were characterized, focusing on curing temperatures of 100 °C, 140 °C, and 180 °C. Mechanical characterization through tensile tests and dynamic mechanical analysis (DMA) revealed varying Young’s modulus (E) (stiffness) and glass transition temperatures (TG) among the ECAs. Electrical characterization showed that lower curing temperatures generally led to lower volume resistivity, particularly for ECA C. However, joint resistance values exhibited high standard deviations. Void analysis indicated that void formation had a negligible effect on the mechanical properties of ECAs. Furthermore, the influence of curing degree on mechanical and electrical properties was investigated, highlighting the importance of complete curing for achieving desired properties. Overall, this study provides valuable insights into optimizing the interconnection process for PVST solar cells, essential for enhancing the long-term stability and performance of solar modules